Can passage in Galleria mellonella activate virulence factors of Paracoccidioides brasiliensis as in the murine model? - Scorzoni, Liliana [UNESP]; De Paula E Silva, Ana Carolina Alves [UNESP]; De Oliveira, Haroldo Cesar [UNESP]; Marcos, Caroline Maria [UNESP]; De Lacorte Singulani, Junya [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Oxford University Press (OUP), 2018)
Paracoccidioidomycosis (PCM) is a fungal disease restricted to Latin countries, and its etiologic agents derive from the Paracoccidioides genus. Attenuation or loss of virulence in Paracoccidioidesspp. following successive subculturing has been described. However, virulence can be recovered by passage in mammalian host. In this study, the recovery of adhesion of P. brasiliensis through passage in mice was compared to that in the insect Galleria mellonella. Analysis of in vitro fungal-host cell interaction, gene expression of adhesins, and analysis of the survival curves revealed that Galleria mellonella is useful for the reactivation of P. brasiliensis adhesion.
Keywords: Adhesins; Fungal-host cell interaction; Galleria mellonella; Mice; Paracoccidioides brasiliensis; Virulence factors